2009
DOI: 10.1002/nbm.1380
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric spin‐echo (ASE) spiral improves BOLD fMRI in inhomogeneous regions

Abstract: Functional MRI (fMRI) is of limited use in areas such as the orbitofrontal and inferior temporal lobes due to the presence of local susceptibility-induced field gradients (SFGs), which result in severe image artifacts. Several techniques have been developed to reduce these artifacts, the most common being the dual-echo spiral sequences (spiral-in/out and spiral-in/in). In this study, a new multiple spiral acquisition technique was developed, in which the later spiral acquisitions are acquired asymmetrically wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Functional MRI was conducted using an asymmetric spin-echo (ASE) spiral sequence that collects three images per slice per volume (Brewer et al, 2009). The three ASE spiral images have equal blood-oxygen level-dependent (BOLD) contrast, but increasing T 2 -weighting.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional MRI was conducted using an asymmetric spin-echo (ASE) spiral sequence that collects three images per slice per volume (Brewer et al, 2009). The three ASE spiral images have equal blood-oxygen level-dependent (BOLD) contrast, but increasing T 2 -weighting.…”
Section: Methodsmentioning
confidence: 99%
“…The three ASE spiral images have equal blood-oxygen level-dependent (BOLD) contrast, but increasing T 2 -weighting. Prior work has shown that increased T 2 -weighting improves sensitivity to WM fMRI activation (Brewer et al, 2009; Gawryluk et al, 2009). Accordingly, the three ASE images were combined using an inverted signal weighted averaging algorithm.…”
Section: Methodsmentioning
confidence: 99%
“…Statistical analyses were done with motion parameters as covariates. 2 Except where otherwise stated, Z statistic images were first developed using a threshold for clusters determined by Z > 2.0 and a (corrected) cluster significance threshold of P = 0.05 (Worsley et al, 1992). Subsequently, activation maps were displayed in MRIcro (Z > 2.5).…”
Section: Functional Mri Data Analysesmentioning
confidence: 99%
“…Seventeen axial slices (4 mm thick, no gap) were prescribed to cover the corpus callosum, as well as the region extending superiorly. Other parameters for functional imaging were: 64 × 64 matrix (220 × 220 mm), 1 shot, 170 volumes, TR/TE/TE = 2000/68/27 ms (TE/TE are the spin-echo centre and asymmetric echo times, respectively; Brewer et al, 2009). …”
Section: Fmri Acquisitionmentioning
confidence: 99%